Diretrizes de usabilidade para o desenvolvimento de jogos sérios com interação gestual destinados à área da saúde - Milani, Fernanda (2018)
In order to serious game professionals develop systems that can be used as tools to promote health and well-being for patients, they need to be oriented to create applications that are appropriate to the profile of the target audience, considering usability characteristics. Keeping that in mind, this work proposes usability guidelines to support serious game development for Health, focusing on gesture-based interaction. The following steps were done in order to conduct this study: a systematic review of the literature on the area; a proposal of guidelines focused on serious game development, based on the results of the systematic review; and a pilot study to do a preliminary evaluation of the guidelines. As a result of this pilot study, it was possible to observe the importance of establishing guidelines for affection, feedback, interaction, identity, challenge, adaptability, narrative, flow and collaboration for serious game planning. We executed comparisons of means between one experimental group and one control group, with four participants each. Considering the small group of subjects of the pilot study, it was valid the definition of basic guidelines proposed of our work, faciliting the game development - particularly in the affection guideline. Although the application of the guidelines did not show statistically significant results in the majority of the proposed guidelines, we observed in the product presented by the experimental group positive results in relation to several aspects of the game interface, meeting the requirements of the proposed guidelines for the development of serious games